Colorectal Cancer is A Leading Cause of Cancer Incidence and Mortality among Adults Younger than 50 Years in the Usa: A Seer-Based Analysis with Comparison to Other Young-Onset Cancers. (February 2017) - Bhandari, Abhishek; Woodhouse, Melissa; Gupta, Samir
Colorectal cancer (CRC) incidence and mortality are rising among young adults. Our aim was to contrast the relative incidence and mortality of CRC to other common cancers among young adults in the USA. We used Surveillance, Epidemiology, and End Results registry data to compare cancer site-specific and age-specific mortality and incident rates for adults younger than age 50. We summarized extracted data, both overall, and stratified by sex. We found CRC was the third leading cause of cancer death among adults younger than age 50, after breast and lung cancer (1.67 cases per 100, 000). Among young women, CRC was the fourth leading cause of cancer death (1.51 per 100, 000). Among young men, CRC was the second leading cause of cancer death (1.82 cases per 100, 000). CRC was the second most incident cancer among young adults for men and women combined. Among men, CRC was the second most incident cancer after age 30, with 4.9, 9.0, 16.4, and 30.8 cases per 100, 000 for ages 30–34, 35–39, 40–44, and 45–49 years, respectively. Among women, CRC incidence was similar with 4.2, 7.6, 15.3, and 25.9 cases per 100, 000 for ages 30–34, 35–39, 40–44, and 45–49 years, respectively. These results show that CRC is a leading cause of cancer incidence and mortality among young adults in the USA, relative to other cancers. Given trends toward increasing rates of CRC among young adults, strategies for identifying individuals at risk for young-onset CRC who might benefit from early age of screening initiation merit investigation.